Efecto de las características del biorreactor y de su manejo sobre el desarrollo de cultivos embriogénicos de alcornoque (V Congreso Forestal Español, 2009)
En el marco del proyecto SEFEAL-2, liderado por TRAGSA, se aplican protocolos de embriogénesis somática (ES) para desarrollar variedades de alcornoque de alta calidad y productividad. Al mismo tiempo se mejora la técnica de ES para abaratar los costes y permitir su aplicación a escala comercial. En el alcornoque, como en otras especies, el desarrollo comercial de la embriogénesis como técnica de multiplicación masiva se basa en el uso de biorreactores y medios líquidos agitados. El diseño del biorreactor, su sistema de cierre y el nivel de agitación determinan el grado de mezclado, el estrés hidrodinámico y el intercambio gaseoso, y por ello afectan tanto al crecimiento como al desarrollo de los cultivos embriogénicos. Mediante un ensayo factorial se testaron 3 tipos de envase y tres niveles de agitación. Los efectos sobre el intercambio gaseoso se estimaron a través de la tasa de transferencia de O2 (OTR) y su coeficiente volumétrico de transferencia de masa (KLa), y los efectos sobre el nivel de mezclado mediante el “shear force index” (SFI), un indicador de estrés hidrodinámico. El tipo de envase afectó básicamente al número total de agregados embriogénicos y a la frecuencia de formación de los agregados de mayor tamaño. El nivel de agitación tuvo mayores efectos que el tipo de envase tanto sobre el número como sobre el tamaño de los agregados. Para las condiciones ensayadas, que dieron lugar a valores de KLa comprendidos entre 0,11 h-1 y 1,47 h-1, la disponibilidad de oxígeno no pareció limitante. En cualquier caso, los efectos del tipo de envase y del nivel de agitación sobre los procesos de crecimiento y desarrollo de los materiales embriogénicos de alcornoque fueron complejos resultando muy significativa la interacción tipo de envase por nivel de agitación

Regeneración clonal de alcornoques selectos mediante embriogénesis somática (V Congreso Forestal Español, 2009)
Para implementar la silvicultura multivarietal se precisa disponer de una metodología de propagación vegetativa eficiente y económicamente viable. La embriogénesis somática se está asentando como la vía de clonación más adecuada para las especies forestales consideradas recalcitrantes. En el IMIDRA hemos logrado poner a punto un protocolo de inducción de embriogénesis somática en hojas de alcornoques adultos, aplicable a cualquier genotipo, que permite clonar árboles selectos. En el marco del proyecto SEFEAL-2, liderado por TRAGSA, se está aplicando este protocolo con el objetivo de clonar 70 árboles seleccionados por su calidad y productividad en procedencias extremeñas, a fin de establecer los oportunos ensayos clonales que permitan evaluar dicho material para su inclusión en el Catálogo Nacional de Materiales de Base, en la categoría controlado. Hasta el momento se ha trabajado con 59 genotipos, en 51 de ellos se han obtenido brotes epicórmicos y por tanto hojas para inducir embriogénesis, lográndose líneas embriogénicas en 44 de estos últimos. Por tanto, al primer intento se ha logrado la inducción en un 86% de los genotipos ensayados. Se indujo embriogénesis en un 17 % de las hojas introducidas en cultivo, variando la frecuencia con el genotipo entre 0 y 56%. Las líneas se amplificaron por embriogénesis recurrente y los embriones, tanto madurados espontáneamente como sometidos a un tratamiento de maduración, fueron estratificados y dispuestos a germinar. Los porcentajes de conversión a plántula oscilaron en función del genotipo entre el 37 y el 75% para los embriones sometidos a un tratamiento de maduración, y entre el 9 y el 87% para los madurados espontáneamente. La supervivencia media de las vitroplantas regeneradas de embriones que maduraron espontáneamente fue del 17%, variando en función del genotipo entre 0 y 33%, mientras que las que procedieron de embriones somáticos sometidos a tratamiento de maduración fue del 26%, oscilando entre el 12 y el 52% según genotipos. Palabras

First data from a field trial of Quercus suber plants regenerated from mature selected trees and from their half-sib progenies by somatic embryogenesis (Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants, 2007)
Somatic embryogenesis is considered as the most suitable current regeneration technique for the conservation and genetic improvement of tree species. The ability to induce somatic embryogenesis in leaves from mature trees gives the possibility to compare the performance of the parent trees and their progenies at the same age and place of test. Somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies. They were planted in the field conjointly with zygotic seedlings of these families, to test the comparisons somatic vs. zygotic origin and somatic from mature trees vs. somatic from juvenile seedlings. The effect of genotype and kind of progeny will be studied in a complete factorial design; therefore the field trial comprised 15 treatments arranged in five completely randomised blocks. Each experimental unit included three plants that were distributed following a row and column pattern. Fist survival and height data after six and twelve months of establishment are provided. All plants from seeds survived while almost the half of somatic seedlings died after the winter and they were replaced. Almost 70% of these plants survived after the following summer. There were no differences between somatic seedlings of mature or juvenile origin. Zygotic seedlings doubled the height of the somatic ones after one year in the field, and within these plants those of mature origin grew slightly more than those of juvenile source. Differences due to genotype and family effects were noticeable. No apparent morphological alterations were detected among the three kinds of tested progenies.

Genetic transformation of selected mature cork oak (Quercus suber L.) trees. (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.

Vegetative propagation of Quercus suber L. by somatic embryogenesis. II. Plant regeneration from selected cork oak trees. (Plant cell reports, 2003)
The regeneration of somatic seedlings from selected 100-year-old cork oak trees is reported. The induction of somatic embryogenesis from leaves of epicormic shoots was significantly affected by genotype, harvesting time and their interaction. Leaves from all five selected trees produced somatic embryos when the segments of branches used as sources of epicormic shoots were collected in May. Genotype, but not the level of photosynthetically active radiation, affected the proliferation of the embryogenic lines and the number of detachable embryos that could be obtained from them. Genotype also affected several steps leading to conversion of somatic embryos, from germination to complete acclimatisation of somatic seedlings. Almost 40% of the somatic embryos from all lines germinated, showing coordinated root and shoot growth. Although the mean percentage of recovery for the whole process was low, plants could be regenerated from four of the five trees tested.

Vegetative propagation of Quercus suber L. by somatic embryogenesis. I. Factors affecting the induction in leaves from mature cork oak trees. (Plant cell reports, 2003)
Somatic embryogenesis was induced in expanding leaves from epicormic shoots forced to sprout from segments of branches collected from several hundred-year-old cork oak trees. Following a basic protocol previously defined for leaves taken from seedlings of this species, several factors were studied to improve the response. The induction frequency was significantly higher when the length of exposure to growth regulators was increased from 7 to 30 days. The combined application of NAA and BAP was essential for induction. Although both regulators had a very significant influence, their interaction was not significant, suggesting independent roles. Leaf size had a crucial effect, because beyond a certain threshold, embryogenesis could not be obtained. Embryogenic lines were maintained via repetitive embryogenesis on hormone-free medium for more than 2 years.

EARLY CHECKING OF GENETIC STABILITY OF CORK OAK SOMATIC EMBRYOS BY AFLP ANALYSIS. (International Journal of Plant Sciences, 2001)
Early checking of the genetic stability, of tissue culture-derived plants is necessary to obtain all the potential benefits of clonal forestry. Previous work in Quercus suber L. using random amplified polymorphic DNA (RAPD) markers showed no genetic variation among somatic embryos within embryogenic lines of zygotic origin. Genetic fingerprinting based on amplified fragment length polymorphisms (AFLP) allows the direct analysis of variation at the entire DNA level by generating more reproducible markers than RAPDs. To confirm the absence of genetic variation within six embryogenic lines of zygotic origin, six primer pairs were selected out of 48 combinations of primers for revealing up to 512 AFLP markers, 301 of them (58.8%) being polymorphic. The mean number of markers per genotype was 375. Again differences were recorded among embryogenic lines, even between those that arose from half-sib zygotic embryos, but no variation was observed among somatic embryos within embryogenic lines. To check variation in embryogenic lines raised from non-embryonic tissues, somatic embryogenesis was induced in expanding leaves collected from sprouts originating in three mature cork oak. DNA was extracted from leaves and from somatic embryos derived from each tree, and three primer pairs showed 165, 110, and 108 markers per genotype/tree, respectively. In one tree, AFLP patterns generated from leaves and somatic embryos were identical, but variation was detected in samples from the other two trees. Although the level of genetic variation detected in these lines (5.6% and 7.3% of polymorphism, respectively) is lower than that recorded for half sibs of cork oak (25%–31%), its influence on phenotypic variation needs further assessment. [ABSTRACT FROM AUTHOR]

Testing the conservation of Quercus spp. microsatellites in the cork oak, Q-suber L. (SILVAE GENETICA, 2001)
The transferability of microsatellite (SSR) loci from Quercus spp. to cork oak (Quercus suber L.) was investigated. Semi-automated analysis of fluorescently-labelled PCR fragments was used to test 24 primer sets developed for Q. myrsinifolia BLUME, Q. petraea (MAT7.) LIEB. and Q. robur L. in 41 cork oak trees from four stands covering the main area of distribution of the species in Spain. Successful cross-species events occurred for 13 loci (54%). Two of them were monomorphic and another two appeared as multilocus. High levels of genetic variability were detected both for the number of alleles, 62 (7.5 per polymorphic locus, with a maximum number of 19 in locus ssrQpZAG110) and for the expected heterozygosity (mean H-E = 0.648). These results were much higher than those previously reported by other authors using allozyme loci. The usefulness of the. SSR loci successfully amplified for studies on population genetics of cork oak is discussed.

OBTENCION DE PLANTAS A PARTIR DE EMBRIONES SOMATICOS DE QUERCUS SUBER L (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
This paper gives a procedure to regenerate plants of cork oak through somatic embryogenesis. The somatic embryos were obtained in leaves from young seedlings and cotyledonary fragments from mature acorns of cork oak. The explants were cultured in three stage process in wich BA and NAA concentration were decreasing. Different methods were used to germinate the embryos. Dessication and culture in low salt concentration medium were chosen to give the best results

Cultivo in vitro del alcornoque (Scientia gerundensis, 1989)
Vegetative plant propagation is mainly used in the operational line of Forest Tree Improvement Programs to capture all the genetic potential, including the non-additive component of the genetic variance. In the case of genus Quercus, it could be also used to avoid the problems derived from installation and yielding of seed orchards. The tissue culture based micropropagation arises as an alternative technique to solve the problems of space and time associated with the classical techniques of asexual propagation. This article reviews the work done with cork-oak in this field. Up to date there are few papers dealing with in vitro culture of Quercus suher L. Embryo culture has been tryed to determine the minimum requeriments of the species and its morphogenic potential. Plantlet regeneration has been obtained following axillary budding on nodal segments from juvenile and rejuvenated tissues, elongation and rooting of microcuttings. Main problems arise on transplanting soil the neoformed plants. Callus culture has been achieved from cotyledons and epicotyl segments from young seedlings. In booth cases also somatic embryogenesis has been reported. This fact opens a new way for micropropagating cork-oak, which is discussed.